Perception of the Language System in ESP Textbooks by Students of IT and Psychology: A Comparative Pilot Study - Kočović Pajević, Milica M.; Obradović, Dušica S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This study examines how IT and psychology students perceive the vocabulary and grammar components of their ESP textbooks, focusing on alignment with their professional and academic needs. By using a Likert scale evaluation checklist, data were collected from 96 students and analyzed in order to identify strengths and weaknesses of the textbooks. Results indicate that while vocabulary represents a strong point in both fields, grammar components, particularly for psychology students, require significant improvement in task variety and contextual relevance. The study highlights the need for tailored textbook design and suggests future research directions to enhance ESP material effectiveness.